2016
DOI: 10.9778/cmajo.20140075
|View full text |Cite
|
Sign up to set email alerts
|

Performance of residents using digital images versus glass slides on certification examination in anatomical pathology: a mixed methods pilot study

Abstract: T he evolution of information technology has revolutionized the practice of pathology. After years of traditional practice using glass slides, we are stepping into a new era of digital images and telepathology.1 Digital pathology can be defined as an image-based information environment enabled by computer technology that allows for the management of information generated from a digital slide. Digital pathology is enabled in part by virtual microscopy, which involves the conversion of glass slides into digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Despite the limited number of publications available confirming whether the paradigm shift has occurred at the residency training level, use of VM is noticeably present in the certification examination of the American Board of Pathology. More recently, the Royal College of Physicians and Surgeons of Canada certification examinations for anatomical pathologists has adopted VM for their national licensing examinations, which posed a query of whether it was essential for residency training programs to provide adequate exposure to prepare their learners with a competent level of VM operation (Hanna et al, ; Mirham et al, ). A Canadian nation‐wide pilot study demonstrated that the performance of pathology residents using VM was statistically comparable to that of using OM (Mirham et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the limited number of publications available confirming whether the paradigm shift has occurred at the residency training level, use of VM is noticeably present in the certification examination of the American Board of Pathology. More recently, the Royal College of Physicians and Surgeons of Canada certification examinations for anatomical pathologists has adopted VM for their national licensing examinations, which posed a query of whether it was essential for residency training programs to provide adequate exposure to prepare their learners with a competent level of VM operation (Hanna et al, ; Mirham et al, ). A Canadian nation‐wide pilot study demonstrated that the performance of pathology residents using VM was statistically comparable to that of using OM (Mirham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the Royal College of Physicians and Surgeons of Canada certification examinations for anatomical pathologists has adopted VM for their national licensing examinations, which posed a query of whether it was essential for residency training programs to provide adequate exposure to prepare their learners with a competent level of VM operation (Hanna et al, ; Mirham et al, ). A Canadian nation‐wide pilot study demonstrated that the performance of pathology residents using VM was statistically comparable to that of using OM (Mirham et al, ). The same study, however, also indicated that a significant number of participating residents had not reached a comfortable level of VM operation, given their current level of VM exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Digital pathology and image analysis have been used widely in the last few years . Pathologists and residents are welcoming the use of digital pathology in their daily practice, and comparable results have been obtained when the performance of residents using glass slides was compared with the results from digital images . This opened the door for a new dimension of sophisticated image‐analysis research, such as genotype/phenotype association analysis and radiohistomics, as detailed in a recent review …”
Section: Research In the Era Of Digital Pathologymentioning
confidence: 99%
“…Bien que les résultats à l'examen simulé n'aient pas démontré de différence significative entre les deux groupes, 95% des participants ont noté des problèmes techniques lors de l'examen sur lames numérisées. Dans un sondage effectué auprès de 179 résidents, tous les répondants considéraient qu'une exposition plus extensive aux lames numériques était nécessaire en vue de se préparer à un examen de certification sur lames virtuelles [7].…”
Section: Texte Encart 3 (Par Rosemarie Tremblay-le May)unclassified